Web Game Implementasi Metode Agile dalam Pembuatan Sistem Game Edukatif Berbasis Web untuk Pembelajaran Bahasa Inggris Tingkat Sekolat Dasar - Pratiwi, Ayu Okta; Qisthiano, M Riski; Aulia, Nanda Aftaa (Universitas Muhammadiyah Magelang, 2025)
This research aims to develop a web-based educational game system aimed at supporting the English language learning process at the elementary school level. The main problem raised is the low interest and motivation of students in learning English through conventional learning methods which tend to be monotonous. To overcome this, a technology-based approach is used by applying Agile methods in the system development process. The Agile method was chosen because it is flexible and allows system development to be carried out gradually and repeatedly according to user needs. The development process includes planning, design, implementation, testing and evaluation stages. The system developed consists of several main features, such as a login page, user dashboard, and game page which includes listening, vocabulary and sentence material. The results of this research show that the system built is able to provide a more interesting, interactive and effective learning experience for elementary school students. Thus, the application of web-based educational game technology can be an alternative solution that supports improving the quality of English learning